Efficient hydrogen production of phosphonitrilic-bridged metal porphyrin porous covalent organic polymer with a push-pull motif. (October 2022) - Wang, Qi; Ren, Jinshen; Wang, Aijian; Dou, Yuqin; Sudi, M. Shire; Zhu, Weihua; Li, Longhua
Abstract: Rational design of efficient hydrogen evolution reaction (HER) electrocatalysts, constructed with earth-abundant elements, is critical for developing sustainable alternative energy sources. Herein, two phosphonitrilic-bridged metal porphyrin porous covalent organic polymers (COPs) were developed for HER. Compared to CoTPP-PCTCOP, NiTPP-PCTCOP exhibits relative low overpotentials of 140 to reach 10 mA cm −2 for HER in alkaline medium, which is comparable to many previously reported state-of-the-art electrocatalysts. The enhanced HER activity of NiTPP-PCTCOP is associated with its chemical composition and special push-pull structure. Long-term stability analysis of NiTPP-PCTCOP shows that the current density exhibits no obvious deactivation over a long time test. This work demonstrates an effective technique to develop promising HER electrocatalysts, highlighting its advantages by combing phosphonitrilic chloride trimer with metal porphyrins. Graphical abstract: Image 1 Highlights: Two phosphonitrilic-bridged metal porphyrin COPs were developed for HER. NiTPP-PCTCOP exhibits relative low overpotentials of 140 to reach 10 mA cm −2 . The effective HER activity is associated with its special push-pull structure.